The Influence of Product Quality and Promotion on Customer Satisfaction and Its Impact on Customer Loyalty PT. Mahakarya Sejahtera Indonesia - Jannah, Rihul; Mappatompo, Andi; Haanurat, Ifayani (Proceeding UII-ICABE, 2020)
This study aims to determine and analyze the effect of product quality and promotion on customer satisfaction and its impact on customer loyalty at PT Mahakarya Sejahtera Indonesia (MSI) as well as knowing and analyzing the variables that influence both directly and indirectly on customer loyalty. Data collection using a questionnaire with the number of respondents was 120 people. The method of analysis used in this study is a quantitative method, through testing the path of analysis. Research shows that product quality has a significant effect on customer satisfaction; promotion has a significant positive effect on customer satisfaction; product quality has no significant effect on customer loyalty; promotion has a significant positive effect on customer loyalty; customer satisfaction has a significant positive effect on customer loyalty; Product quality has a significant positive effect on customer loyalty through customer satisfaction; and promotion has a significant positive effect on customer loyalty through customer satisfaction. Keywords: Product Quality, Promotion, Satisfaction and Loyalty.